2018
DOI: 10.1103/physrevd.98.074504
|View full text |Cite
|
Sign up to set email alerts
|

What symmetry is actually broken in the Higgs phase of a gauge-Higgs theory?

Abstract: In SUðNÞ gauge-Higgs theories, with a single Higgs field in the fundamental representation, there exists in addition to the local gauge symmetry a global SU(2) symmetry, at N ¼ 2, and a global U(1) symmetry, for N ≠ 2. We construct a gauge-invariant order parameter for the breaking of these global symmetries in the Higgs sector and calculate numerically the transition lines, in coupling-constant space, for SU(2) and SU(3) gauge theories with unimodular Higgs fields. The order parameter is nonlocal, and, theref… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…We thus assume that considering operators of the described classes do indeed describe localizable particles and are sufficient to describe all particle-like excitations in any given quantum number channel. Concerning the status for other operator classes in theories of the type considered here, we refer to [37,38] for recent investigations.…”
Section: The General Recipementioning
confidence: 99%
“…We thus assume that considering operators of the described classes do indeed describe localizable particles and are sufficient to describe all particle-like excitations in any given quantum number channel. Concerning the status for other operator classes in theories of the type considered here, we refer to [37,38] for recent investigations.…”
Section: The General Recipementioning
confidence: 99%
“…For a more extensive presentation of the work summarized here, please see refs. [6,8]. Figure 7: For SU(2) gauge-Higgs theory, C confinement exists above the line denoted "Dirac," and S c confinement exists in a strong-coupling region, as well as along the line at β = 0.…”
Section: Discussionmentioning
confidence: 99%
“…This is based on strong-coupling expansions and the Gershgorim Theorem in linear algebra. The argument is, however, a little lengthy, and for that we must refer the reader to section VI in our article [6]. The second question is whether S c confinement holds everywhere in the β − γ phase diagram.…”
Section: S C Confinementmentioning
confidence: 98%
“…A clear symmetry-based distinction between the confining and Higgs phases in a gauge theory with fundamental representation matter fields has been recently proposed in Refs. [110,280,281]. An important generalised criterion of confinement valid in both pure YM theories and YM theories with matter in the fundamental representation states that…”
Section: Separation-of-charge Confinement Criterionmentioning
confidence: 99%
“…In Refs. [110,280,281], it has been shown that a transition between the Cand S c -confinement phases must take place in the gauge-Higgs theory, and the unbroken custodial symmetry has been found to separate the S c -confining (if not massless) phase from the Higgs phase corresponding to a C-confined spin glass state, where the custodial symmetry is actually broken. It would be very interesting to see how such a new concept of S c -confinement can be applied for more realistic theories such as QCD.…”
Section: Separation-of-charge Confinement Criterionmentioning
confidence: 99%